2020
DOI: 10.1001/jamanetworkopen.2020.22927
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Birth Defects and Cancer Risk in Children Conceived via In Vitro Fertilization in the US

Abstract: Key Points Question Is the incidence of birth defects and childhood cancer among children conceived via in vitro fertilization different from that among children conceived naturally? Findings In this population-based cohort study of 1 053 415 children in 4 states, the presence of a birth defect and the number of birth defects were associated with an increased risk of childhood cancer. The increased risk was 2-fold higher for children conceived via in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Through IPA analysis, we found the differential methylation of genes enriched in biological process categories such as synthesis of lipid, synthesis of steroid, secretion of lipid and secretion of molecule, which provided a possible explanation of the abnormal lipid metabolism of IVF progeny. A meta-analysis conducted in 2013 showed that increased risks for leukemias (RR = 1.65; 95% CI, 1.35-2.01), neuroblastoma (RR = 4.04; 95% CI, 1.24-13.18), and retinoblastomas (RR = 1.62; 95% CI, 1.12-2.35) were associated with fertility treatment (Hargreave et al, 2013;Luke et al, 2020). Consistent with our predictions, we found that differentially methylated sites were enriched in the pathways of chronic myeloid leukemia, activation of lymphocytes, and activation of mononuclear leukocytes by GO/KEGG and IPA analyses, which may cause immunological abnormalities, providing a possible explanation for increased incidence of cancer in IVF progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through IPA analysis, we found the differential methylation of genes enriched in biological process categories such as synthesis of lipid, synthesis of steroid, secretion of lipid and secretion of molecule, which provided a possible explanation of the abnormal lipid metabolism of IVF progeny. A meta-analysis conducted in 2013 showed that increased risks for leukemias (RR = 1.65; 95% CI, 1.35-2.01), neuroblastoma (RR = 4.04; 95% CI, 1.24-13.18), and retinoblastomas (RR = 1.62; 95% CI, 1.12-2.35) were associated with fertility treatment (Hargreave et al, 2013;Luke et al, 2020). Consistent with our predictions, we found that differentially methylated sites were enriched in the pathways of chronic myeloid leukemia, activation of lymphocytes, and activation of mononuclear leukocytes by GO/KEGG and IPA analyses, which may cause immunological abnormalities, providing a possible explanation for increased incidence of cancer in IVF progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Children born after ART now account for 2% of all births. Indisputable data have confirmed elevated neonatal and childhood morbidity in ART pregnancies, including preterm birth, intrauterine growth restriction (IUGR), perinatal mortality, low birth weight (LBW), small for gestational age (SGA), catch-up, congenital abnormalities, dyslipidemia, certain cancers, altered blood pressure, thyroid and cardiovascular dysfunction (Moini et al, 2012;Pandey et al, 2012;Kawwass et al, 2013;Kondapalli and Perales-Puchalt, 2013;Hu et al, 2014a;Lv et al, 2014Lv et al, , 2016Xu et al, 2014;Rubens et al, 2014;Meng et al, 2015;Luke et al, 2020). The possible explanations are complex because there are many confounding factors, including ovarian stimulations, laboratory procedures manipulating gametes and embryo culture (Iliadou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper suggested that a rapid drop in methylation can be observed in human embryos shortly after fertilization [22]. This is based on data obtained from IVF embryos and may be an artifact of culture conditions [2,11,23]. Under natural conditions, the methylation status is stabilized by maintenance of methylation.…”
Section: Problems Associated With Assisted Reproductive Technologymentioning
confidence: 99%
“…Both reports suggest that these disorders may originate in the period immediately following fertilization under culture conditions in current use [20]. The possible source of these problems has been clearly advocated [2,11,23,24]; firstly, controlled ovarian stimulation increases the level of homocysteine (Hcy) in follicular fluid [25]. Hcy competes with methionine for the same amino acid transporter [26], which leads to abnormal accumulation of Homocysteine in the oocyte.…”
Section: Problems Associated With Assisted Reproductive Technologymentioning
confidence: 99%
“…According to European Society of Human Reproduction and Embryology (ESHRE), nearly 776,000 assisted reproductive technology (ART) cycles and 175,000 intrauterine insemination (IUI) cycles were performed in Europe each year [2]. The higher incidence of cancer and congenital disability observed during the in vitro fertilization (IVF) cycles reminds us of careful consideration [3][4][5]. IUI, a safe and relatively low-cost procedure, is often the rst-line in infertility treatment for couples with unexplained infertility, low-grade endometriosis, sexual function disorders, and low-grade male subfertility [6].…”
Section: Introductionmentioning
confidence: 99%